2017
DOI: 10.5137/1019-5149.jtn.21895-17.2
|View full text |Cite
|
Sign up to set email alerts
|

How to reduce stress on the pedicle screws in thoracic spine? importance of screw trajectory: a finite element analysis

Abstract: AT decreased the von-Mises stress of the pedicle screws, thereby reducing the rates of screw breakage and fatigue risks. In addition, we believe that AT could protect against screw loosening because the von-Mises stress of the internal fixation was scattered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…9 Furthermore, the von Mises stress distributions on screws were calculated which ranged from 48.7 to 317.3 MPa in agreement with previous studies. 34,35 The average von Mises stresses for shaft of screws in the level with maximum experienced applied force/moment are listed in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…9 Furthermore, the von Mises stress distributions on screws were calculated which ranged from 48.7 to 317.3 MPa in agreement with previous studies. 34,35 The average von Mises stresses for shaft of screws in the level with maximum experienced applied force/moment are listed in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…In clinical practice, screw loosening and breakage are common reasons for revision of internal spinal fixation. Reducing the stress on the screws could reduce the risk of screw breakage and loosening 33 , 34 , 35 . Therefore, we also investigated the peak stress in the interbody cage and screw‐bone interface in Models A, B, and C with different implantation regions.…”
Section: Discussionmentioning
confidence: 99%
“…For the stress of internal fixation system, flexing, extension, left axial rotating and right axial rotating were the noteworthy working conditions that caused stress concentration. The difference of the pedicle screws’ points and orientations contributed mostly to the difference in stress distribution 39 , 40 . When the different points and orientations were selected, stress distribution of pedicle screws and rods would be changed consequently.…”
Section: Discussionmentioning
confidence: 99%
“…This study result tied well with previous studies wherein the same was observed from all the three different postoperative models. Similarly, the rods connecting two pairs of pedicle screws up and down were under the major stress 39 . In the FE study section, the mean stress values of the three groups (Roy-Camille, Magerl, and Krag) were 80.12 MPa, 92.77 MPa and 66.80 MPa, respectively.…”
Section: Discussionmentioning
confidence: 99%